100 power tips for FPGA designers. - Stavinov, Evgeni, ....- ([s.l.] : Evgeni Stavinov, 2011)
This book is a collection of short articles on various aspects of FPGA design: synthesis, simulation, porting ASIC designs, floorplanning and timing closure, design methodologies, performance, area and power optimizations, RTL coding, IP core selection, and many others. The book is intended for system architects, design engineers, and students who want to improve their FPGA design skills. Both novice and seasoned logic and hardware engineers can find bits of useful information. This book is written by a practicing FPGA logic designer, and contains a lot of illustrations, code examples, and scripts. Rather than providing information applicable to all FPGA vendors, this book edition focuses on Xilinx Virtex-6 and Spartan-6 FPGA families. Code examples are written in Verilog HDL. All code examples, scripts, and projects provided in the book are available on accompanying website: http://outputlogic.com/100_fpga_power_tips